(untitled) (The Review of Diabetic Studies, 2024)
Background: Anterior Cruciate Ligament (ACL) rupture represents a pervasive and debilitating musculoskeletal pathology, disproportionately affecting the young, athletic population globally. The injury incidence has seen a concerning rise, particularly among adolescents and high-demand athletes involved in pivoting sports such as soccer, basketball, and skiing, with an estimated annual incidence of 1 in 3,500 individuals. The resulting functional instability and long-term sequelae, including meniscal degradation and early-onset osteoarthritis, pose a significant burden on healthcare systems and individual quality of life. Objective: The primary objective of this systematic review is to comprehensively compare the effectiveness of Intervention 1 (accelerated physiotherapy, operative innovation, and enhanced nursing care) versus Intervention 2 (standard/delayed care) on key clinical and radiological outcomes. Specifically, the review aims to correlate post-surgical MRI findings—serving as biomarkers for graft ligamentization and structural integrity—with functional recovery outcomes (Lysholm scores, IKDC scores, knee laxity) to determine if accelerated functional recovery compromises biological graft maturation. Methods: A systematic review was conducted in strict adherence to PRISMA 2020 guidelines. A comprehensive search was performed across major electronic databases. The PICO framework was utilized. Methodological quality was assessed using the Cochrane Risk of Bias tool for RCTs, the Methodological Index for Non-Randomized Studies, and the Modified Coleman Methodology Score for rehabilitation protocols. Results: The synthesis of included studies reveals a complex, non-linear relationship between structural integrity and functional performance. Accelerated rehabilitation protocols were found to significantly improve early functional outcomes, with patients demonstrating superior Lysholm and IKDC scores and faster recovery of muscle strength at 3-6 months post-surgery compared to standard protocols. However, this functional acceleration appeared to come at a structural cost; meta-analytic data indicated a statistically significant increase in instrumental knee laxity and bone tunnel widening in the accelerated groups. MRI analysis demonstrated that graft "ligamentization" is a prolonged biological process, with signal intensity peaking at approximately 6 months regardless of the protocol, indicating a mismatch where patients are functionally capable before their grafts are biologically mature. Enhanced nursing care, particularly structured education and psychological support, was identified as a critical modifier, significantly improving patient adherence to rehabilitation restrictions and positively correlating with subjective functional scores. Conclusion: The findings suggest that while accelerated physiotherapy and advanced surgical techniques successfully expedite functional recovery and patient satisfaction, they induce greater mechanical stress on the remodeling graft, evidenced by increased laxity and tunnel enlargement. A "functional-biological mismatch" exists wherein the clinical improvements outpace biological graft maturation. Consequently, clinical practice should shift towards a criterion-based progression model that integrates MRI monitoring of graft volume and maturation, supported by robust nursing education to ensure adherence. Future research must prioritize longitudinal studies to ascertain whether the increased laxity observed in accelerated protocols translates to higher rates of long-term osteoarthritis or graft failure.